Confecção de estruturas tubulares permeáveis de PLGA - Schardosim, Mariane Giacomini (2012)
Peripheral nerve injury accident is a common type of lesion that can cause loss of mobility and decrease the quality of life. Despite advances in the biomedical area, there are few cases where there is complete functional recovery of a damaged nerve. The application of biodegradable polymers such as poly(lactide-co-glycolide) (PLGA), shows a viable alternative of treatment in peripheral nerves injuries for presenting mechanical strength, biocompatibility and controlled degradation, being also an excellent material for drug delivery. A PLGA scaffold should be porous with pore sizes on the order of micro-and nanometer, which offers the possibility to insert growth factors, promoting a constant release of these biological structures. The aim of this research is to produce porous scaffolds of PLGA. This was achieved by dissolving the polymer in chloroform, adding a porogenic compound. A titanium rod with 2mm in diameter was deeped in the suspension obtained and dried in a hood, obtaining a layer of PLGA / porogen agent on the surface of the rod. In sequence, the rod was immersed in a solution of PLGA with chloroform. After dried for 2 hours in a hood, the titanium rods were submerged in deionized water for 48 hours, during which the water was changed every 8 hours in order to remove the porogenic agent. After this process, the tubular structures formed were easily removed from the rods. Finally, the prepared tubes were divided into groups and treated with different concentrations of sodium hydroxide, to create pores in the order of nanometers, and subsequently vacuum dried for 48 hours. The structures obtained were characterized by XRD, FTIR, SEM and the in vitro degradation was monitored by GPC.